2018
DOI: 10.1177/1541931218621240
|View full text |Cite
|
Sign up to set email alerts
|

Mini Breaks, Many Benefits: Development and Pilot Testing of an Intraoperative Microbreak Stretch Web-Application for Surgeons

Abstract: Periodic intraoperative microbreaks with calesthenic exercises performed within the sterile field improved self-reported mental focus (38%) and physical performance (57%) for 56 surgeons. Therefore, targeted stretching exercises and a web-application (web-app) leading the stretches with a reminder system were developed and piloted using user-centered design principles. A focus group with 10 users was conducted to refine the developed app. Seven surgeons (4 females) at a quaternary medical institute piloted the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…NMSDs have been found to be the most common health problem reported by surgeons (general, colorectal, vascular, and cardiothoracic) that led to retirement [ 6 ]. Experts in this research area (e.g., health care ergonomists) should dedicate more effort to the development and evaluation of potential interventions such as ergonomic education [ 10 , 36 , 37 ], intraoperative stretching microbreaks [ 11 14 ], and exercises before and after the surgical procedures [ 10 ] to mitigate surgeons’ body part discomfort/pain and the risk of developing NMSDs. Furthermore, exploring the NMSDs among four surgical modalities showed that its prevalence was significantly lower in robotic surgeons (7%) compared to the other surgical modalities (between 60 and 67%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NMSDs have been found to be the most common health problem reported by surgeons (general, colorectal, vascular, and cardiothoracic) that led to retirement [ 6 ]. Experts in this research area (e.g., health care ergonomists) should dedicate more effort to the development and evaluation of potential interventions such as ergonomic education [ 10 , 36 , 37 ], intraoperative stretching microbreaks [ 11 14 ], and exercises before and after the surgical procedures [ 10 ] to mitigate surgeons’ body part discomfort/pain and the risk of developing NMSDs. Furthermore, exploring the NMSDs among four surgical modalities showed that its prevalence was significantly lower in robotic surgeons (7%) compared to the other surgical modalities (between 60 and 67%).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the increasing prevalence of work-related injuries reported by surgeons, there is a critical need for better ergonomic understanding and interventions in the operating room (OR). While previous studies have explored potential ergonomic interventions such as physical exercise outside the OR [ 10 ], intraoperative stretching microbreaks [ 11 14 ] and more recently passive exoskeletons [ 15 17 ], there still remain many factors contributing to this problem. One unanswered question is: does surgeon preference for a surgical modality (e.g., open, laparoscopic, endoscopic, robot-assisted) affect the incidence of NMSDs, pain, and physical discomfort?…”
mentioning
confidence: 99%
“…Abdelall et al in their study showed that the web-application microbreak stretches helped to reduce physical pain, discomfort/pain, and fatigue and improve mental focus with minimal disruption among the surgeons [ 29 ]. In addition, Tavakkol et al, in their study on the operating room personnel, revealed that regular exercise and physical activity, use of stretching, and gentle exercise could be practical approaches to relieving the WMSs [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Two more recent studies focused on the development of either an optimised active work-break structure 30 or a web-based application that video guide the surgeon to perform some stretch work breaks. 31 …”
Section: Introductionmentioning
confidence: 99%